The Readiness of Cooperatives in Digitalizing Smallholder Palm Oil Plantations - Falatehan, A Faroby; Hariyadi, Hariyadi; Syaukat, Yusman; Feridian, Sriwulan; Astiti, Pipin Dwi (KnE Social Sciences, 2021)
The era of the industrial revolution 4.0 is marked by a smart industrialization process, which refers to increasing automation, machine-to-machine and human-to-machine communication, implementing artificial intelligence, and developing sustainable digital technology. Increasing the productivity of smallholder oil palm plantations with the application of the right technology will deliver optimal results to improve the welfare of farmers and independent smallholders. This research focused on increasing productivity through digitizing smallholder oil palm plantations. The research was conducted in Siak Regency, Riau Province. This study analyzed the readiness of the Village Cooperative (KUD) of Tunas Muda, including the weaknesses and strengths, as well as the opportunities and threats (SWOT) that existed in preparing for the digitization of smallholder palm oil plantations in Siak Regency. Keywords: industrial revolution 4.0, KUD Tunas Muda, smallholder oil palm digitalization, institutional dimension, SWOT